2016
DOI: 10.3390/ijerph13060523
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis, Urinary Cancer, and Home Drinking Water Source in the United States Territory of Guam, 2006–2010

Abstract: We reviewed patient records with a first-listed diagnosis of urolithiasis—also known as urinary tract or kidney stone disease, nephrolithiasis—upon discharge from Guam’s sole civilian hospital during 2006 to 2010 and urinary cancer mortality records from the Guam Cancer Registry for 1970 to 2009 to determine the source of municipal water supplied to the patients’ residence. The objective was to investigate a possible relationship between the sources of municipal water supplied to Guam villages and the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Reduction of fluid intake of less than 2L/day can cause urine to be concentrated and stone formation. 7,10,25 Similarly, the used of seasoning powder in cooking can increase the level of sodium intake daily, which cause frequent urination, dehydration, fluid loss and urine supersaturation. 25 Based on the findings above, it is important to reduce the incidence of urolithiasis by educating the general public, especially the patients.…”
Section: Knowledge Of Respondents On Urolithiasismentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of fluid intake of less than 2L/day can cause urine to be concentrated and stone formation. 7,10,25 Similarly, the used of seasoning powder in cooking can increase the level of sodium intake daily, which cause frequent urination, dehydration, fluid loss and urine supersaturation. 25 Based on the findings above, it is important to reduce the incidence of urolithiasis by educating the general public, especially the patients.…”
Section: Knowledge Of Respondents On Urolithiasismentioning
confidence: 99%
“…1,5,6 There are several risk factors associated with urolithiasis, which includes genetic, age, gender, body mass index (BMI), weight, water intake, medical morbidities, occupation, hot climate and dietary intake. [2][3][4][5][6][7][8][9][10][11][12][13] Although genetic plays important role in the development of urolithiasis, nevertheless, dietary and lifestyle pattern is believed to have strong association with its occurrence. [9][10][11][12][13] Based on findings from previous studies, a recurrent episode may occur within five years after the first onset, especially among population at hot climate regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6/7 OALib Journal supplied wholly or partially from deep wells was about twice that of villages supplied with municipal water exclusively from a river fed reservoir [19].…”
Section: /7mentioning
confidence: 99%
“…Concerning the quantity indeed, an increased consumption of water and/or other waterbased beverages (and conversely, an increased urinary volume) up to about two liters per day is considered one of the most important preventive measures for stone incidence and recurrence [8,9]. Concerning the quality, different studies have reported and suggested a possible association between stone formation and several physicochemical parameters of drinking water [10,11]. Water hardness, in particular, has been proposed to play a pivotal role [12].…”
Section: Introductionmentioning
confidence: 99%